2017
DOI: 10.1111/apa.13698
|View full text |Cite
|
Sign up to set email alerts
|

Management of early‐onset neonatal sepsis differs in the north and south of Scandinavia

Abstract: There were marginal differences in the management of EONS between units in Denmark and Norway, mainly in their choice of antibiotics and the use of lumbar punctures. Staphylococcus aureus was the most common pathogen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…A number of different studies published since 2012 report that infants receiving systemic antibiotic therapy for culture-negative sepsis outnumber infants receiving therapy for culture-confirmed sepsis by a factor of six to 16 (Table 1 ). The reason for the high number of culture-negative cases is not clear, and diagnostic criteria used in the different publications vary substantially ( 10 , 11 , 23 , 24 , 26 , 27 ). Low levels of bacteremia or only small volumes of blood obtained from sick infants may be one explanation for the high number of culture-negative sepsis cases.…”
Section: Efficient Sepsis Care—basic Elementsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of different studies published since 2012 report that infants receiving systemic antibiotic therapy for culture-negative sepsis outnumber infants receiving therapy for culture-confirmed sepsis by a factor of six to 16 (Table 1 ). The reason for the high number of culture-negative cases is not clear, and diagnostic criteria used in the different publications vary substantially ( 10 , 11 , 23 , 24 , 26 , 27 ). Low levels of bacteremia or only small volumes of blood obtained from sick infants may be one explanation for the high number of culture-negative sepsis cases.…”
Section: Efficient Sepsis Care—basic Elementsmentioning
confidence: 99%
“…The UK NICE-guidelines states that the usual duration of antibiotic treatment for babies with a positive blood culture, and for those with a negative blood culture but in whom there has been strong suspicion of sepsis, should be 7 days ( 8 ). In observational studies, infants with culture-negative sepsis are commonly treated for 5–7 days and mortality is very low ( 10 , 11 , 23 ). However, due to variable sepsis definitions it is not possible to assess “safety” vs. a clear possibility of harm due to overtreatment ( 69 ).…”
Section: Antimicrobial Stewardship In the Neonatal Unitmentioning
confidence: 99%
“…Outpatient antibiotic use in Norwegian children has decreased significantly during the recent years [6]. Studies in Scandinavian inpatient term born infants indicate that antibiotic use can be reduced and that empirical treatment for sepsis varies [7,8]. Furthermore, Raastad et al revealed a significantly increased consumption of BSA in a highly specialized Norwegian pediatric department [9].…”
Section: Introductionmentioning
confidence: 99%
“…In choice of antibiotics, adherence to local hospital guidelines was high and the use of BSA was low. Previous studies show that several Norwegian hospitals use benzylpenicillin instead of ampicillin in empirical treatments combined with an aminoglycoside (11,16,40), and this variation is also present world-wide (41). High prevalence of Listeria monocytogenes could justify the use of ampicillin, but according to data from The Norwegian Institute of Public Health, only four cases of listeriosis have been reported among Norwegian children (< 1 year) from 2011 to 2018 (42).…”
Section: Discussionmentioning
confidence: 99%